Gastrointestinal Fistulas—What Gastroenterologists Need to Know in 2025 - Monjur Ahmed (Canadian Journal of Gastroenterology and Hepatology)
Gastrointestinal fistulas are increasingly being encountered in our clinical practice because of the increased burden of Crohn’s disease, bariatric surgeries, interventional endoscopic procedures, nonsurgical trauma, and war and disaster zones worldwide. Presentation depends on the location and specific type of the fistula. Symptomatic ones can have a tremendous impact on social life and can cause dehydration, electrolyte imbalance, malnutrition, increased morbidity, and mortality. Different imaging studies and endoscopic procedures are done to establish the diagnosis. Treatment modalities to close the fistula depend on the underlying disease and the type of fistula. They include conservative treatment, medical therapy, endoscopic interventions, and surgery. Currently, there is no accepted treatment algorithm due to a lack of controlled clinical trials. The prognosis varies from fistula to fistula, and the mortality can be as high as 50%.